2006
DOI: 10.1007/s11434-006-0675-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of locus S-b for F1 pollen sterility in rice (Oryza sativa L.)

Abstract: Hybrid sterility is the main barrier in utilizing the heterosis of subspecies in rice. A knowledge of the underlying molecular mechanism of the hybrid sterility will be useful for overcoming the barrier. In this research, the F 1 pollen sterility locus, S-b, was mapped between SSR markers PSM8 and PSM202. To fine map the locus, one F 2 mapping population of 3910 plants was developed using the near-isogenic lines of the locus. Ninety-seven recombinants between two markers were selected. Moreover, a series of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
1
31
0
3
Order By: Relevance
“…In addition it has been found that another locus, S35 on chromosome 1, enhances pollen sterility through an interaction with S24 (Kubo et al 2008). Using different cross combinations of indica and japonica varieties, other researchers have reported on hybrid male sterility genes named f5-Du (Wang et al 2006) and Sb (Li et al 2006), which map to the S24 region on chromosome 5. S24, f5-Du, and Sb occur within a single 90-kb region and are therefore likely to be the same gene (Zhao et al 2010).…”
mentioning
confidence: 99%
“…In addition it has been found that another locus, S35 on chromosome 1, enhances pollen sterility through an interaction with S24 (Kubo et al 2008). Using different cross combinations of indica and japonica varieties, other researchers have reported on hybrid male sterility genes named f5-Du (Wang et al 2006) and Sb (Li et al 2006), which map to the S24 region on chromosome 5. S24, f5-Du, and Sb occur within a single 90-kb region and are therefore likely to be the same gene (Zhao et al 2010).…”
mentioning
confidence: 99%
“…Li et al (2006) fine-mapped a locus Sb, hybrid pollen sterility gene, in the region of 27 kb of the same PAC clone, P0008A07 using a population derived from a cross between Taichung 65 and its near isogenic line TISL2. The targeted S24-containing regions of the three mapping results were overlapped by a fragment of 6.4 kb (Fig.…”
Section: High-resolution Mapping Of S24 Locusmentioning
confidence: 99%
“…Among these are the widely accepted 'double recessive gamete lethal' (Oka 1974) and the 'allelic interaction' (Ikehashi and Araki 1986) models. Others have singled out embryo-sac abortion (Wan et al1993;Ikehashi 1995, Wan et al 1996;Yanagihara et al 1992;Liu et al 2001;Zhu et al 2005;Zhao et al 2007;Li et al 2007) or pollen sterility (Li et al 2006Wang et al 2006;Jing et al 2007;Win et al 2009). According to the allelic interacting model, F 1 hybrid sterility results from the interaction at an SX locus of the i (indica) and j (japonica) allele.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Qiu et al (2005) were able to delimit S5 to a 40-kb DNA fragment, by constructing a population from a three-way cross based on NILs for the S5 locus. Similarly, S-b (responsible for F 1 pollen sterility) could be located to 27-kb region (Li et al 2006). An alternative approach takes advantage of chromosome segment substitution lines (CSSLs) which comprise a series of genotypes in a common genetic background carrying overlapping chromosome segments derived from a donor genotype.…”
Section: Introductionmentioning
confidence: 99%